Pengaruh Teknik Penanakan terhadap Sifat Fisik (Tekstur dan Warna) Nasi dari Beras Analog Berbahan Baku Tepung Sorgum, Mocaf, Glukomanan, dan Kelor: The Effect of Cooking Techniques on the Texture and Color of Analog Rice Made from Sorghum, Mocaf, Glucommanan, and Moringa Flour - Khoirunnisah, Frisqi Meilany; Aji, Arif Sabta; Saloko, Satrijo; Aprilia, Veriani; Sailendra, Nova Veronika; Djidin, Radhiyya Tsabitah S.; Rahmawati, Sri (Amerta Nutrition, 2024)
Background: Rice cooking techniques determine the physical properties acceptance. A healthy diabetic diet such as the consumption of analog rice with the benefits of functional food can help control blood sugar. Thus, the physical properties of analog rice are important.  Objectives: To determine the effect of cooking techniques on the physical properties (texture and color) of analog rice made from sorghum, Modified Cassava Flour (Mocaf), glucomannan, and moringa flour.  Methods: This experimental study used a completely randomized design (CRD). It used two rice cooking treatments (steamer and rice cooker) on analog rice and C4 rice with two repetitions of both treatment and analysis. This research was conducted during October-November 2022. The physical properties of rice, namely texture and color were tested using a texture analyzer and chroma meter. Data were analyzed statistically using the Mann-Whitney test with the help of SPSS version 23.0.  Results: The cooking technique did not affect the rice texture in terms of hardness bite 1, springiness, and chewiness of both analog rice and C4 rice (p-value>0.05). However, the cooking technique affected the color of analog rice (p-value<0.05), but it did not apply to C4 rice (p-value>0.05).  Conclusions: Both steaming and rice cooker techniques do not affect the physical texture of analog rice and C4 rice. However, the cooking techniques significantly influence the color of analog rice. The addition of moringa leaves to analog rice shows a significant difference in the color of both analog rice and C4 rice.